AFTER 16 YEARS: AN UPDATE CHECKLIST OF HERPETOFAUNA ON THE NATUNA ISLANDS, INDONESIA - Alamsyah E. N. Herlambang; Awal Riyanto; Misbahul Munir; Amir Hamidy; Kaeda Kimura; Koshiro Eto; Mumpuni Mumpuni (BRIN Publishing (Penerbit BRIN), 2022)
Since the last list of amphibians and reptiles of the Natuna Islands was published nearly 20 years ago, here we provide an updated species list of the herpetofauna of these remote Indonesian islands. We compiled and summarized data from the available literature, and from our own studies conducted in 2011, 2012, 2013, 2017, and 2019. In total, 120 species of amphibians and reptiles were recorded for the Natuna Islands, which included 28 new records and six endemics. Over the past eight years, four species new to science were described from these islands, and they are: Cnemaspis mumpuniae, Cnemaspis sundainsula, Cyrtodactylus hikidai, and Cyrtodactylus rosichonariefi.